Global neuro-oncology: what lies ahead for low- and middle-income countries? - Syed Ather Enam; Kee B. Park; Naureen Mushtaq; Muhammad Faraz Raghib; Fatima Mustansir; Mashal Murad Shah; Mohammad Hamza Bajwa; Minhal Faisal; Michael C. Dewan; Tariq Khan; et al. (Journal of the Pakistan Medical Association, 2024)
Over the past few decades, the global healthcare community has achieved remarkable success in controlling many communicable diseases across various regions. However, non-communicable diseases now constitute a significant portion of disease morbidity and mortality, particularly in low- and middle-income countries (LMICs). Among these, cancer, in particular, is witnessing a notable increase in incidence in many LMICs. Among cancers, neurological tumours bear significant impact in terms of long-term disability, escalating costs of comprehensive multidisciplinary care, and often encounter resource-related and systemic delays in care leading to worse outcomes. This opinion paper discusses key concepts in developing global neuro-oncology care, with specific case examples from Pakistan to illustrate methods for improving care in these underserved regions. Additionally, it outlines strategic approaches and potential solutions to address these challenges, aiming to provide a roadmap for enhancing neuro-oncology care in LMICs. Keywords: Ursidae, Incidence, Noncommunicable Diseases, Communicable Diseases,Health Care, Neoplasms, neurosurgery